Editorial - Chew, Shin Yi (Journal of Modern Languages, 2022)
In this first issue of 2022, Journal of Modern Languages (JML) is pleased to share six interesting articles which are of relevance to the field of languages and linguistics. The first article of Volume 32, Department Store Surveys as a Methodology in the Study of Linguistic Variation by Shangxin Zheng and Xiaomei Wang, evaluates the use of Department Store Surveys (DSS) as an effective sociolinguistic tool to study linguistic variation in a multilingual society. Then, the next article by Vivian Chiew and Cecilia Cheong talks about the socio-cognitive and professional practice perspectives on chairperson statements. The findings of their study do not only illuminate the importance of professional discourse but also highlight pedagogical implications for English for Professional Communication (EPC) programmes. In this issue, we have also included an article that concern minority languages, a major area of interest for many researchers. In the article Maimani Language and Lawati Language: Two Sides of the Same Coin?, Said Humaid Al Jahdhami shares with us the resemblance between two minority languages which are Maimani Language and Lawati language. The other two articles focus on translation. In the article Evaluating the Curriculum for M.A. English Translation in Iran: Is the Curriculum Effective for Students?, Aynaz Samir evaluates the effectiveness of the English translation programme in Iran by investigating 341 university students’ perspectives. Insights for curriculum reform in the area of English translation are provided. The following article The Art of Paper Cutting: Strategies and Challenges in Chinese to English Subtitle Translation of Cultural Items by William Chai, Hui Yi Ong, Mansour Amini and Latha Ravindran highlights the technical, cultural and linguistic challenges faced in translating culture-specific items. Some of the proposed strategies in dealing with the translation of culture-specific terms are omission, equivalence, adaptation and direct transfer. Last but not least, Abbas Pazireh, Nilofar Hessamodini and Zohre Jaferi reported the findings of their quantitative study in the article Iranian EFL Learners’ Perceptions towards Demotivation in Learning English. In their study, 300 Iranian high school students’ perceptions of demotivation in learning English were gathered and factors such as teachers, textbooks, classroom conditions were identified. We hope that these articles published by JML are insightful to you and that you would share them with your friends and colleagues. For your easy reference, a list of featured articles published in the last five years is attached in the Appendix.